AW/EP behavior of WS2 nanoparticles added to vegetable oil-based lubricant - Gulzar, Mubashir; Hassan, Masjuki; Kalam, Md. Abul; Munusamy, Mahendra Varman; Mufti, Riaz Ahmad; Zahid, Rehan; Yunus, Robiah (Malaysian Tribology Society, 2015)
Improvement in the anti-wear (AW) and extreme pressure (EP) ability of chemically modified jatropha oil (CMJO) by adding nanoparticles was experimentally evaluated. Nano-lubricants were synthesized by adding 1 wt% tungsten disulfide (WS2) nanoparticles to CMJO. The AW/EP ability of trial oils were evaluated using four-ball wear tests. Wear surfaces were analyzed by scanning electron microscopy (SEM) along with energy-dispersive X-ray (EDX). The addition of 1 wt% oleic acid as surfactant (S) assisted in reducing the agglomerates. The addition of WS2 nanoparticles improved AW/EP properties of CMJO.